PD-L1 in tumor microenvironment mediates resistance to oncolytic immunotherapy - Zamarin, Dmitriy; Ricca, Jacob M.; Sadekova, Svetlana; Oseledchyk, Anton; Yu, Ying; Blumenschein, Wendy M.; Wong, Jerelyn; Gigoux, Mathieu; Merghoub, Taha; Wolchok, Jedd D. (The Journal of clinical investigation, 2018)
Intralesional therapy with oncolytic viruses (OVs) leads to the activation of local and systemic immune pathways, which may present targets for further combinatorial therapies. Here, we used human tumor histocultures as well as syngeneic tumor models treated with Newcastle disease virus (NDV) to identify a range of immune targets upregulated with OV treatment. Despite tumor infiltration of effector T lymphocytes in response to NDV, there was ongoing inhibition through programmed death ligand 1 (PD-L1), acting as a mechanism of early and late adaptive immune resistance to the type I IFN response and T cell infiltration, respectively. Systemic therapeutic targeting of programmed cell death receptor 1 (PD-1) or PD-L1 in combination with intratumoral NDV resulted in the rejection of both treated and distant tumors. These findings have implications for the timing of PD-1/PD-L1 blockade in conjunction with OV therapy and highlight the importance of understanding the adaptive mechanisms of immune resistance to specific OVs for the rational design of combinatorial approaches using these agents.